Nanomedicine in HNSCC therapy-a challenge to conventional therapy - Li, Chenyu; Fang, Yuan; Xu, Sanchun; Zhao, Jingyuan; Dong, Deshi; Li, Shuai (Frontiers in Pharmacology, 2024)
Squamous cell carcinoma of the head and neck (HNSCC) is a difficult-to-treat cancer and treatment is challenging due to recurrence or metastasis. Therefore, there is an urgent need to explore more effective targeted therapies to improve the clinical outcomes and survival of HNSCC patients. The nanomedicine is emerging as a promising strategy to achieve maximal anti-tumor effect in cancer therapy. In this review, we summarize some important signaling pathways and present the current and potential roles of various nanomaterial drug-delivery formulations in HNSCC treatment, aiming to understand the pathogenesis of HNSCC and further improve the therapeutic efficacy of nanomaterial HNSCC. This article seeks to highlight the exciting potential of novel nanomaterials for targeted cancer therapy in HNSCC and thus provide motivation for further research in this field.